Strong out-of-plane magnetic anisotropy in ion irradiated anatase TiO2 thin films - M. Stiller; J. Barzola-Quiquia; P. Esquinazi; D. Spemann; J. Meijer; M. Lorenz; M. Grundmann (AIP Advances, 2016)
The temperature and field dependence of the magnetization of epitaxial, undoped anatase TiO2 thin films on SrTiO3 substrates was investigated. Low-energy ion irradiation was used to modify the surface of the films within a few nanometers, yet with high enough energy to produce oxygen and titanium vacancies. The as-prepared thin film shows ferromagnetism which increases after irradiation with low-energy ions. An optimal and clear magnetic anisotropy was observed after the first irradiation, opposite to the expected form anisotropy. Taking into account the experimental parameters, titanium vacancies as di-Frenkel pairs appear to be responsible for the enhanced ferromagnetism and the strong anisotropy observed in our films. The magnetic impurities concentrations was measured by particle-induced X-ray emission with ppm resolution. They are ruled out as a source of the observed ferromagnetism before and after irradiation.